2017
DOI: 10.1080/10715762.2017.1282158
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrite modulates miRNA signatures in acute myocardial in vivo ischemia/reperfusion

Abstract: Acute myocardial infarction is the leading cause of mortality in the industrialized world. While it is essential to attempt an early reperfusion of ischemic myocardial territories, reperfusion itself adds damage to the heart, the ischemia-reperfusion (I/R) injury. Particularly the injury resulting from the very first minutes of reperfusion remains incompletely understood. MicroRNAs (miRNAs) are dynamic regulators in I/R injury. Nitric oxide ( NO) signaling, in turn, interacts with miRNA signaling. Our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The role of miR-125a-3p, miR-324-3p, and miR-139-3p in cardioprotection is still unclear. Previous reports demonstrated that circulating miR-125a-5p was associated with heart failure 29 , and it was significantly upregulated in early phase of reperfusion in mice 30 . An other recent study demonstrated that miR-139-5p is downregulated in left ventricular tissue isolated from patients undergoing remote conditioning 31 .…”
Section: Discussionmentioning
confidence: 88%
“…The role of miR-125a-3p, miR-324-3p, and miR-139-3p in cardioprotection is still unclear. Previous reports demonstrated that circulating miR-125a-5p was associated with heart failure 29 , and it was significantly upregulated in early phase of reperfusion in mice 30 . An other recent study demonstrated that miR-139-5p is downregulated in left ventricular tissue isolated from patients undergoing remote conditioning 31 .…”
Section: Discussionmentioning
confidence: 88%
“…Further, for miR qRT-PCR data, a fold change of 1.2 is generally used as cutoff instead of the 2-fold cutoff for mRNAs, since it is believed that small differences in miR levels are sufficient for the fine-tuning of the transcriptional system executed by miRs. Various studies have shown miRs with a fold change ~1.2 to be biologically relevant [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous, small, noncoding RNAs that could modulate gene expression post‐transcriptionally, leading to mRNA degradation or translational inhibition . Progressive evidence indicates that the abnormal levels of miRNAs occur in myocardial infarction, which are involved in regulating the oxidative stress and inflammation in MIRI .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous, small, noncoding RNAs that could modulate gene expression post-transcriptionally, leading to mRNA degradation or translational inhibition. 12 Progressive evidence indicates that the abnormal levels of miRNAs occur in myocardial infarction, which are involved in regulating the oxidative stress and inflammation in MIRI. 13,14 miRNA-200a is found to protect myocardial cells against hypoxia-induced apoptosis through activating nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway.…”
mentioning
confidence: 99%